2016
DOI: 10.1049/el.2015.3727
|View full text |Cite
|
Sign up to set email alerts
|

6–18 GHz, 8.1 W size‐efficient GaN distributed amplifier MMIC

Abstract: A 6-18 GHz, 8.1 W gallium nitride (GaN) distributed amplifier (DA) monolithic microwave integrated circuit (MMIC) is presented with compact size. To accomplish high-output power density with compact size, the last two sections of the DA consist of small-sized FETs. This approach improves the output return loss and allows the drain line lengths to be reduced thereby increasing the drain cutoff frequency and reducing circuit size, which results in increased gain and output power characteristics up to higher freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Each NDA consists of eight gain cells to optimise the linear gain, bandwidth and output power. As mentioned in our previous work, unequal‐sized FETs are applied in the NDA to improve the output return loss and the power gain at a high frequency without drain line termination impedances [9]. The proposed NDA mostly uses 6 × 75 μm GaN high electron mobility transistors (HEMTs), but the last section has a 2 × 125 μm GaN HEMT.…”
Section: Circuit Designmentioning
confidence: 99%
“…Each NDA consists of eight gain cells to optimise the linear gain, bandwidth and output power. As mentioned in our previous work, unequal‐sized FETs are applied in the NDA to improve the output return loss and the power gain at a high frequency without drain line termination impedances [9]. The proposed NDA mostly uses 6 × 75 μm GaN high electron mobility transistors (HEMTs), but the last section has a 2 × 125 μm GaN HEMT.…”
Section: Circuit Designmentioning
confidence: 99%
“…Together with its unique characteristics, especially higher breakdown voltage and higher output power density, it has been proven to be an excellent candidate in high frequency applications [ 5 ]. Numerous circuit designs based on GaN processes with outstanding performance have sprung out these recent years [ 6 , 7 , 8 ]. The rapid development of GaN-based devices also stimulates the improvement of compact modeling, which serves as a key to practical circuit design [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green et al (2001) demonstrated the capability of a three-section cascade DA, which was able to deliver an output power of 6 W and a gain of 12 dB in a frequency range of 2-8 GHz. The distributed power amplifier (DPA) concept also has been explored in the monolithic microwave integrated circuit (MMIC) form where a 0.25-m m gallium nitride (GaN)-based DA is able to deliver 8.1 W output power and 6.1 dB average gain across 6-18 GHz (Kim et al, 2016). Broadband bidirectional DA by Shou et al exhibits small-signal gain of 14.4 dB from 1.6 to 23.6 GHz (Weng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%